High Coxiella burnetii Seroconversion Rate in Veterinary Students, the Netherlands, 2006–2010 - Marit M.A. de Lange; Wim van der Hoek; Peter M. Schneeberger; Arno Swart; Dick J.J. Heederik; Barbara Schimmer; Inge M. Wouters (Emerging Infectious Diseases, 2020)
We examined Coxiella burnetii seroconversion rates by measuring C. burnetii IgG among 2 cohorts of veterinary students. During follow-up of 118 seronegative veterinary students, 23 students seroconverted. Although the clinical importance of the presence of antibodies is unknown, veterinary students should be informed about the potential risks for Q fever.